Addressing the Shortage of Speech-Language Pathologists in School Settings - Squires, Katie (Journal of the American Academy of Special Education Professionals, 2013)
There is a shortage of speech-language pathologists (SLPs) in this country. This shortage is due, in part, to the limited number of openings in graduate programs and the increased need for SLPs as their scope of practice widens, the autism rate grows, and the population ages. Schools are feeling this shortage the most. There are several reasons school districts have a hard time attracting and retaining SLPs. This paper will offer possible solutions to attract more candidates to the field including expanding graduate school options. It will also address options to fill positions such as using teletherapy services or speech-language assistants. School speech-language pathologists (SLPs) are typically licensed by a health board in the state in which they are employed, are sometimes also licensed by their state’s Department of Education, are usually certified by the American Speech-Language Hearing Association, and hold Master’s degrees in communicative disorders. While there are 257 academic institutions that grant Master’s degrees, there is still a nationwide shortage of qualified SLPs, with New York, California, Illinois, Florida and Texas having the greatest unmet need (Wolfgang, 2011). In 10 years’ time, there is predicted to be a 27% increase in job openings and employment for SLPs is expected to grow faster than the average for all other occupations (Edgar & Rosa-Lugo, 2007). This scarcity of SLPs in a nationwide concern because most SLPs are employed in school settings, and when schools cannot employ enough qualified individuals the students’ needs either go unmet, or students are served by untrained persons.